Development of a Fluorescent Microfluidic Device Based on Antibody Microarray Read-Out for Therapeutic Drug Monitoring of Acenocoumarol - Salvador, J.-Pablo; Brettschneider, Thomas; Dorrer, Christian; Marco, M.-Pilar (Frontiers in Bioengineering and Biotechnology, 2022)
The development of a proof-of-concept point-of-care (PoC) device for the determination of oral anticoagulants determination is presented. Acenocoumarol (ACL) is prescribed to prevent certain cardiovascular diseases related to the prevention of deep vein thrombosis, pulmonary embolism, myocardial infarction, and stroke. Oral anticoagualant treatment (OAT) represents a population of 2% under treatment which has expenditures about 144 million in 2011. The main drawback for OAT is the associated narrow therapeutic window and the unpredictable dose-response relationship, which is one of the main causes for visiting the emergency room at the hospitals. In a previous work, family antibodies were produced for the simultaneous detection of ACL and warfarin (W) depending on the area of application. It was developed in different formats, indirect and direct, either with similar detectabilities and both assays quantifying the oral anticoagulants with high accuracy and reproducibility. We present the implementation of the already developed immunochemical method to a point-of-care (PoC) device to assist on the patient compliance assessment programs. In order to achieve this goal, a first development was performed implementing ACL ELISA assay into a microarray format with fluorescent read-out. The assay was successfully implemented achieving a LOD of 1.23 nM of ACL directly measured in human plasma. Then, a fully integrated microfluidic system is developed which incorporates the specific immunoreagents for the detection of ACL. The immunoreagents were attached onto the glass slide in a microarray format. The system is automatic, rapid, sensitive, and disposable that could help clinicians monitor patients under OAT. According to the fluorescent label of the ACL binding, the chip can be easily read with a scanner. The microfluidic system performed good according to the robust and reproducible signals, and subsequently yielded an accurate result.